Single-phase high power-factor boost ZCS pre-regulator operating in critical conduction mode - Canesin, C. A.; Goncalves, FAS (IEEE, 2003)
This paper presents a new single-phase interleaved high power factor boost pre-regulator operating in critical conduction mode, where the switches and boost diode performing zero-current commutations during its turn-off, eliminating the disadvantages related to the reverse recovery losses and electromagnetic interference problems of the boost diode, when operating in the continuous conduction mode. The interleaving technique is applied in the power cell, providing a significant input current ripple reduction in comparison to discontinuous mode of operation, due to its input current continuous conduction operation. This paper presents a complete modeling for the converter operating in critical conduction mode, resulting in an improved design procedure for interleaved techniques with high input power factor, a complete design procedure, and main simulation results from a design example with two interleaved cells rated at 1kW, 400V output voltage and 220V rms input voltage.
Keywords: interleaved techniques; active power factor correction; boost zcs-fm; critical conduction mode